Diet quality, change in diet quality and risk of incident CVD and diabetes - Xu, Zhe (Public Health Nutr, 2020)
OBJECTIVE: The objective of this study was to assess the prospective association between diet quality, as well as a 6-year change in diet quality, and risk of incident CVD and diabetes in a community-based population. DESIGN: We used Cox regression models to estimate the prospective association between diet quality, assessed using the Healthy Eating Index (HEI)-2015 and the Alternative HEI (AHEI)-2010 scores, as well as change in diet quality, and incident CVD and diabetes. SETTING: The ARIC Study recruited 15 792 black and white men and women (45–64 years) from four US communities. PARTICIPANTS: We included 10 808 study participants who reported usual dietary intake via FFQ at visit 1 (1987–1989) and who had not developed CVD, diabetes, or cancer at baseline. RESULTS: Overall, 3070 participants developed CVD (median follow-up of 26 years) and 3452 developed diabetes (median follow-up of 22 years) after visit 1. Higher diet score at the initial visit was associated with a significantly lower risk of CVD (HR per 10 % higher HEI-2015 diet quality score: 0·90 (95 % CI: 0·86, 0·95) and HR per 10 % higher AHEI-2010 diet quality score: 0·96 (95 % CI: 0·93, 0·99)). We did not observe a significant association between initial diet score and incident diabetes. There were no significant associations between change in diet score and CVD or diabetes risk in the overall study population. CONCLUSIONS: Higher diet quality assessed using HEI-2015 and AHEI-2010 was strongly associated with lower CVD risk but not diabetes risk within a middle-aged, community-based US population.